2016
DOI: 10.3389/fmicb.2016.01859
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Gut Microbiota Colonization with Broad-Spectrum Cephalosporin Resistant Enterobacteriaceae in a Tunisian Intensive Care Unit

Abstract: Healthcare-associated infections due to cefotaxime-resistant (CTX-R) Enterobacteriaceae have become a major public health threat, especially in intensive care units (ICUs). Often acquired nosocomially, CTX-R Enterobacteriaceae can be introduced initially by patients at admission. This study aimed to determine the prevalence and genetic characteristics of CTX-R Enterobacteriaceae-intestinal carriage in ICU patients, to evaluate the rate of acquisition of these organisms during hospitalization, and to explore so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Most studies have shown that a long hospital stay increases the risk for colonization or infection with MDR bacteria [2,5]. In fact, Day 30 to screen patients was chosen, on the basis of those studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have shown that a long hospital stay increases the risk for colonization or infection with MDR bacteria [2,5]. In fact, Day 30 to screen patients was chosen, on the basis of those studies.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were then screened for ESBL production using both the resistance phenotype and the double-disk synergy test by the use of conventional combination [5]. …”
Section: Microbiological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…K. pneumoniae isolates of clonal complex 17 are well recognized contributors to the spread of CTX-M-15 worldwide [31] and ST336 is among the less prevalent yet international clones that have been associated with the spread of various ESBL enzymes, including CTX-M-15, and even carbapenemase resistance [23,32,33]. K. pneumoniae ST336 has been reported in blood, urine, stool, exudate, intraabdominal and respiratory tract specimens and an unknown specimen from 45 patients in North America, Europe and Asia [27,28,[31][32][33][34][35][36]. While 14 of the cases were sporadic and seemingly unrelated, one Portuguese study revealed an almost yearlong nosocomial and clonal outbreak that affected mostly kidney transplant patients and patients with urinary tract disorders; the organism was isolated from urine in 27 of the 31 case patients [31].…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Virulence factors were studied in eight of the 45 reported isolates of K. pneumoniae ST336. An intraabdominal isolate was found to encode type 1 fimbriae [32], which are common in the species and essential for the development of urinary tract infections [37], and a faecal isolate was found to encode type 3 fimbriae, responsible for biofilm formation [38], and the siderophores enterobactin and yersiniabactin [36]. Six isolates from blood were negative for the capsular antigens K-1 and K-2, which may be associated with hypervirulence in some clonal complexes [39].…”
Section: A C C E P T E Dmentioning
confidence: 99%